2014
DOI: 10.1080/00958972.2014.961921
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vibrational spectra (FT-IR and VCD) and nonlinear optical properties of [Ru(L)3]2+ complexes

Abstract: Density functional theory calculations were performed on [Ru(L) 3 ] 2+ (L = 1,10-phenanthroline, 2,2′-bipyridine, 2,2′-bipyrimidine, 2,2′-bipyrazine) complexes by employing B3PW91 functional and LAN2DZ basis set to predict their spectra and nonlinear optical response. The geometrical and coordination energy studies explained that the stability of [Ru(L) 3 ] 2+ metal complexes depends on the extent of interaction of the dπ orbitals of Ru 2+ with the π* ligand orbitals, which is maximum for 1,10-phenanthroline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…On the other hand, a correlation coefficient of 0.91 (or higher) is observed for electron-withdrawing groups. According to Ulman, the [63,64]. The donor group will easily push electrons towards the aromatic system and remain itself slightly electron deficient.…”
Section: Nonlinear Responsementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a correlation coefficient of 0.91 (or higher) is observed for electron-withdrawing groups. According to Ulman, the [63,64]. The donor group will easily push electrons towards the aromatic system and remain itself slightly electron deficient.…”
Section: Nonlinear Responsementioning
confidence: 99%
“…The total static dipole moment (μ), average linear polarizability (α) and first-order hyperpolarizability (β) using the x, y, z components of the compound from Gaussian 03 W [60] output were calculated by Eqs. 4-6 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%
“…Polarizability and hyperpolarizability characterises the response of a system in an applied field. It is well known for various studies that the molecular polarizability, hyperpolarizability and dipole moments are important for active nonlinear performance of the chemical system [64,65]. Helical system (TOH and TTH) contained sp 2 -hybridised carbon, the electron in the p z -orbital of each sp 2 -hybridised carbon atom will form p-bonds with the neighbouring p z -electrons.…”
Section: Frontier Molecular Orbitals Uv-visible Spectra Charge Tranmentioning
confidence: 99%
“…Currently, considerable attention has been focused on the studies of organic molecules capable of exhibiting organic light emitting properties or massive NLO susceptibilities. Researchers have observed that the presence of extended π-electron delocalization is the key element in the design of organic molecules exhibiting either the OLED or NLO applications (Geffroy et al, 2006 ; Sasabe and Kido, 2011 , 2013a , b ; Jin and Tang, 2013 ; Sekine et al, 2014 ; Islam and Pandith, 2014a ; Romain et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Octaphyrin (1.1.1.1.1.1.0.0) ( OP ), being a conjugated π system may be the excellent candidate for the materials science. Many research groups have reported the synthesis and structural properties of isomers of Octaphyrin (1.1.1.1.1.1.0.0) (Franck and Nonn, 1995 ; Latos-Grazynski, 2004 ; Shimizu et al, 2005 ; Rath et al, 2005b ; Geffroy et al, 2006 ; Hiroto et al, 2006 ; Kumar et al, 2007 ; Misra and Chandrashekar, 2008 ; Anaka et al, 2011 ; Sasabe and Kido, 2011 , 2013a , b ; Mori et al, 2012a ; Jin and Tang, 2013 ; Kido et al, 2013 ; Naoda and Osuka, 2014 ; Sekine et al, 2014 ; Islam and Pandith, 2014a ; Anguera et al, 2015 ; Romain et al, 2015 ). According to Chandershaker et al the core-modified expanded porphyrins containing 26, 36, and 54 π electrons because of their exceptionally massive two-photon absorption cross- sections may be considered among the most effective appropriate candidates, particularly as organic NLO materials (Pushpan and Chandrashekar, 2002 ).…”
Section: Introductionmentioning
confidence: 99%